Assessing the Comparative Advantage of Sheep Industry in Al-Hasakah District, Syria: A Policy Analysis Matrix Approach - Hammo, Alaa; Abdul-Aziz, Ali; Nasser, Shabab (Annals of Arid Zone, 2022)
This study aimed to assess the comparative advantage of Sheep industry in Al-Hasakah district, Syria. The primary data for an average 2017/2018 and 2018/2019 were collected using a questionnaire designed for this purpose, distributed to the sample size of 313 rearers, they were selected using simple random sampling method, from the administrative areas of Al-Hasakah district. The results showed the nominal protection coefficient on tradable outputs (NPCO) equal to 0.77 that indicated the policies have caused the domestic output price to be less than the social price by 0.23. While the nominal protection coefficient on tradable inputs (NPCI) equal to 1.05, that showed the domestic input cost is greater than the input cost at social prices and the system is taxed by policy. The effective protection coefficient (EPC) equal to 0.62 that indicates the net effect of policies that alter prices in product markets is to reduce private profits by 0.38, and the combined transfer effect is thus negative, and the domestic resource cost (DRC) value of 0.11, which indicated that the study area has a comparative advantage in Sheep industry.